Underlying Resistance Mechanisms in the Cynosurus echinatus Biotype to Acetyl CoA Carboxylase-Inhibiting Herbicides - Fernández, Pablo; Alcántara-de la Cruz, Ricardo; Cruz-Hipólito, Hugo; Osuna, María D.; De Prado, Rafael (Frontiers in Plant Science, 2016)
Hedgehog dogtail (Cynosurus echinatus) is an annual grass, native to Europe, but also widely distributed in North and South America, South Africa and Australia. Two hedgehog dogtail biotypes, one diclofop-methyl (DM)-resistant and one DM-susceptible were studied in detail for experimental dose-response resistance mechanisms. Herbicide rates that inhibited shoot growth by 50% (GR50) were determined for DM, being the resistance factor (GR50R/GR50S) of 43.81. When amitrole (Cyt. P450 inhibitor) was applied before treatment with DM, the R biotype growth was significantly inhibited (GR50 of 1019.9 g ai ha-1) compared with the GR50 (1484.6 g ai ha-1) found for the R biotype without pretreatment with amitrole. However, GR50 values for S biotype do not vary with or without amitrole pretreatment. Dose-response experiments carried out to evaluate cross-resistance, showed resistance to aryloxyphenoxypropionate (APP), cyclohexanodione (CHD) and phenylpyrazoline (PPZ) inhibiting herbicides. Both R and S biotypes had a similar 14C-DM uptake and translocation. The herbicide was poorly distributed among leaves, the rest of the shoot and roots with unappreciable acropetal and/or basipetal DM translocation at 96 HAT. The metabolism of 14C-DM, D-acid and D-conjugate metabolites were identified by thin-layer chromatography. The results showed that DM resistance in C. echinatus is likely due to enhanced herbicide metabolism, involving Cyt. P450 as was demonstrated by indirect assays (amitrole pretreatment). The ACCase in vitro assays showed that the target site was very sensitive to APP, CHD and PPZ herbicides in the C. echinatus S biotype, while the R biotype was insensitive to the previously mentioned herbicides. DNA sequencing studies confirmed that C. echinatus cross-resistance to ACCase inhibitors has been conferred by specific ACCase double point mutations Ile-2041-Asn and Cys-2088-Arg.